2021
DOI: 10.1136/bmjdrc-2020-002026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of undiagnosed type 2 diabetes and pre-diabetes on severity and mortality for SARS-CoV-2 infection

Abstract: IntroductionDiabetes and hyperglycemia are risk factors for critical COVID-19 outcomes; however, the impact of pre-diabetes and previously unidentified cases of diabetes remains undefined. Here, we profiled hospitalized patients with undiagnosed type 2 diabetes and pre-diabetes to evaluate its impact on adverse COVID-19 outcomes. We also explored the role of de novo and intrahospital hyperglycemia in mediating critical COVID-19 outcomes.Research design and methodsProspective cohort of 317 hospitalized COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 38 publications
5
59
0
1
Order By: Relevance
“…A longer observation period of 30 days yielded comparable results and conclusions since the mortality was significantly higher in patients with type 2 diabetes than in the group without (13.6% vs 8.7%; p < 0.001) as reported by Sonmez et al [11]. Moreover, pre-diabetes and undiagnosed type 2 diabetes were also found to be risk factors for severe SARS-CoV-2 infection [8].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A longer observation period of 30 days yielded comparable results and conclusions since the mortality was significantly higher in patients with type 2 diabetes than in the group without (13.6% vs 8.7%; p < 0.001) as reported by Sonmez et al [11]. Moreover, pre-diabetes and undiagnosed type 2 diabetes were also found to be risk factors for severe SARS-CoV-2 infection [8].…”
Section: Discussionsupporting
confidence: 69%
“…A onemonth-long study (February 26, 2020, to March 26, 2020) conducted by Akbariqomi et al [7] in a hospital in Iran found that 1 in 4 COVID-19 patients had diabetes (148 of 595; 24.9%). In a study by Vargas-Vázquez et al [8] based in a Mexican COVID-19 centre during the March-July period of 2020, 50.2% of patients had type 2 diabetes (159 out of 317), with more than one-third of them being previously undiagnosed. However, such a high rate may have been a result of strict patient inclusion criteria as 600 patients were excluded due to e.g., lack of HbA1c measurement on admission.…”
Section: Discussionmentioning
confidence: 98%
“…As reported in the literature, an interaction between COVID-19 and glucose-insulin metabolic disorders is postulated in adults [1,29] and not excluded in pediatrics [30,31]. In particular, the relationship between COVID-19 and type 2 diabetes mellitus (T2DM) has been extensively described in adults [1,2,30] and a relationship between SARS-CoV-2 infection and type 1 diabetes mellitus (T1DM) has also been discussed in children [30][31][32][33][34][35][36]. This is possibly the first up-to-date study on the relationship between IR and glycemic fluctuation in normal weight children without glycemic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In a multi-centre study in Austria, of 47 patients with prediabetes (HbA1c 5.7–6.4% on admission), 7 (14.9%) had in-hospital death [ 16 ]. In a study from Mexico, of 125 patients with prediabetes (HbA1c 5-0.7-6.4% on admission), 27 (21.6%) died during hospitalization [ 17 ]. In a study from Dubai, 2 out of 10 (20%) patients with prediabetes (prior diagnosis or HbA1c 5.7–6.4% on admission) had in-hospital death [ 18 ].…”
Section: Discussionmentioning
confidence: 99%